Conceptual approaches to diagnosis and preventive treatment of hip subluxation and dislocation in children with infantile cerebral palsy - Korolkov, Oleksandr; Liutkevich, Mykola; Khashchuk, Andrey (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2013)
A conceptual model of diagnosis and preventive treatment for hip subluxation and dislocation in children suffering from infantile cerebral palsy (ICP) is presented and recommendations for its application are given. The authors used a syndromic approach for developing this model, created a classification of medical measures in cases of hip subluxation and dislocation in children with ICP and suggested their typical combinations. Owing to the conducted study it became possible to systematize a complex set of symptoms of different changes, revealed in children with ICP, as well as to substantiate and create conceptual approaches to diagnosis, treatment and prognostication of hip joint pathology depending upon the neurological status, anatomic-functional and age-related peculiarities of the child’s organism. The developed concept makes it possible to specify and detail a diagnosis, thereby giving grounds for using an individual set of medical (conservative and surgical) measures aimed at improvement of the anatomic-functional state of a patient with ICP. The authors plan to carry out clinical verification of the suggested concept in further reports.